Thinking and doing beyond science and risk communication as mere transmission - Ponce de Leon, Inez (2024)
Access online through this link: http://plarideljournal.org/article/thinking-and-doing-beyond-science-and-risk-communication-as-mere-transmission
Keywords: Scientific communication; Research; Data science